Source Base of Historical and Pedagogical Research on the Formation and Development of Teachers Education in Podillya in the Second Part of XIX Century - Beginning of Twentieth Century - Balabust, Natalya (Pedagogical Discourse, 2013)
The article is based on the analysis of the materials of the state archives from Kyiv, Vinnytsia and Khmelnytsky regarding the development of Podillya education sector during the process of region incorporation into Russian state system. Also the article highlights formation of teachers’ training education during the mentioned period, impact of the imperial policy of the tsarist government on teachers’ training education, infrastructure and material provision of the educational institutions, social and financial status of the tearchers in the region. The most useful archives in this regards are from collections 707 , 442 , 315 , 301 of the Central State Historical Archive in Kyiv, colleactions 55, 57, 63, 64, 65, 66, 67, 228, 233 ,315,319, 684 of Khmelnytsky Regional State Archive, collections 16, 20 , 48, 54, 698 of Vinnytsia Regional State Archive.